The Role of Social Capital in Students’ Higher Education Decision - Rawat, Gyanendra (International Journal of Psychosocial Rehabilitation, 2020)
Expanding higher education cooperation has brought about endeavors coordinated towards expanding advanced education access. Nonetheless, the disparity in the completion of higher education keeps on existing. Social capital has been found to be significant in deficiencies in an individual’s interest in higher education access. Given the role of social capital, we need to inspect the higher education choice after the higher-secondary level from a social capital and social help viewpoint with family, traditional and strict affiliations, companions, and personnel assuming a part in advanced education access. The impact of social capital on academic continuation in education is examined in this paper. The definition of social capital is discussed in the study in light of this. As a result, it outlines how the social capital theory came to be, how it developed, and how it relates to education. Much research inspected how social capital influences higher education after secondary and post-secondary levels. This review inferred that those high degrees of social capital found in parents and networks affect higher education, even in the wake of representing pay, parental education, and student participation. This article specifies a structure depicting how network individuals from higher secondary groups complete one another concerning assets offered and add to higher education access.